2015
DOI: 10.1016/j.neuroimage.2015.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory signatures of crossmodal congruence effects: An EEG investigation employing a visuotactile pattern matching paradigm

Abstract: Coherent percepts emerge from the accurate combination of inputs from the different sensory systems. There is an ongoing debate about the neurophysiological mechanisms of crossmodal interactions in the brain, and it has been proposed that transient synchronization of neurons might be of central importance. Oscillatory activity in lower frequency ranges (<30Hz) has been implicated in mediating long-range communication as typically studied in multisensory research. In the current study, we recorded high-density … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 62 publications
4
41
0
Order By: Relevance
“…Given that we only analysed activity within 500 ms after change onset, this negative finding concurs with the results of Göschl et al 11 who found visual-tactile congruence effects building up only after 400 ms to 1100 ms11. (Unfortunately, we could not analyse this later time window in our data because it overlaps with the presentation of the second intensity change.)…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Given that we only analysed activity within 500 ms after change onset, this negative finding concurs with the results of Göschl et al 11 who found visual-tactile congruence effects building up only after 400 ms to 1100 ms11. (Unfortunately, we could not analyse this later time window in our data because it overlaps with the presentation of the second intensity change.)…”
Section: Discussionsupporting
confidence: 90%
“…In typical studies demonstrating early multisensory congruence effects, mostly detection or categorisation tasks are employed in which cross-modal congruence per se is task-irrelevant1046. Overall, the results of Göschl et al 11 and from our study indicate that if cross-modal congruence is task-relevant, early multisensory congruence effects seem to be diminished.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Early sensory processing should reflect the aforementioned gain adjustments and thus should not differ between attentional conditions. Congruence relations should systematically affect cortical processing at later stages of processing, for instance in temporal, parietal and/or frontal regions (Göschl, Friese, Daume, König, & Engel, 2015).…”
Section: Multisensory Integration and Processing Stagesmentioning
confidence: 99%